Postoperative glycemic control in cardiac surgery patients - Breithaupt, Theresa (Baylor Health Care System, 2010)
Glycemic control in postoperative cardiac patients is necessary to improve outcomes in wound infection and overall mortality. In recent years, clinical trials evaluating blood glucose control in critically ill patients advocated for intense blood glucose management and found a significant reduction in morbidity and mortality. Some organizations published recommendations regarding blood glucose management in critically ill patients reflecting this information. However, recent clinical trials evaluating blood glucose target ranges in critically ill patients have found conflicting results, which has prompted reevaluation of current goals and guidelines, allowing for less stringent blood glucose target ranges. With the inconsistency of clinical trials evaluating a target blood glucose range for critically ill patients, specifically postoperative cardiac surgery patients, the target blood glucose range is still not clearly defined. Additional comparisons of specific glucose ranges would allow for a clearer definition of recommended blood glucose goals to target in postoperative cardiac patients.